Evaluation of Liquid Versus Dry Specimen Transport With a Newly Validated Isothermal Amplification High-Risk Human Papillomavirus Assay. Issue 3 (July 2020) - Sun, Jingfen; Wu, Suhui; Hu, Longhua; Shang, Haixia; Yang, Yufeng; Pretorius, Robert; Huang, Yaling; Yang, Xi; Wu, Xiaoqin; Belinson, Jerome
Abstract : Objective: The aim of the study was to determine whether the proportion of positive high-risk human papillomavirus (HR-HPV) tests in endocervical specimens transported dry differs from paired specimens transported in liquid media. Methods: Five hundred women aged of 30 to 55 years were recruited, Shanxi Bethune Hospital, China. Two samples were collected from the endocervix per patient, one placed into empty vial, the other into a liquid transport solution. All samples were analyzed by AmpFire HR-HPV assay. Results: Total 1, 000 samples collected from 500 patients were analyzed by the AmpFire HR-HPV assay. The total invalid rate was 0.2% (2/1, 000). The proportion of endocervical samples testing positive for HR-HPV transported dry (42.2%, 210/498 [95% CI = 37.8%–46.6%]) was similar to the proportion of paired endocervical samples testing positive transported in liquid media (40.4%, 201/498 [95% CI = 36.0%–44.8%], p = .18 [McNemar test]). That the 2 transport methods are likely measuring the same positive (and negative) specimens is suggested by the finding that κ value for the correlation of positive HR-HPV in endocervical specimens transported dry with those transported in liquid media was 0.86 (95% CI = 0.81–0.90). Conclusions: Endocervical specimens transported dry have similar proportion of positive HR-HPV tests as those transported in liquid media. Dry brush transport of endocervical samples paired with the special characteristics of AmpFire HR-HPV may become an important addition to population based cervical cancer screening.